AS AN IMPORTANT ELEMENT OF THE CRIMINALISTIC DESCRIPTION OF CASES OF CRIMES COMMITTED IN THE FIELD OF CONSTRUCTION - Karaev Alisher Khursandovich (PT. Antis International Publisher, 2024)
General Background: Economic crimes in the construction sector pose significant challenges due to their complexity and the substantial financial impact they can have. Specific Background: This article addresses the intricate nature of economic crimes within the construction industry, focusing on the specific circumstances, investigative requirements, and criminalistic elements involved. Knowledge Gap: Despite extensive research on economic crimes, there is a lack of comprehensive analysis on the unique investigative challenges and tactical approaches specific to the construction sector. The current literature does not sufficiently address the effective planning, execution, and psychological aspects of investigating such crimes. Aims: The primary aim of this article is to explore the distinctive features of economic crimes in construction, including the necessary evidentiary circumstances, investigative methods, and tactical approaches. It seeks to provide a detailed framework for developing investigative versions and effectively planning and conducting investigative actions. Results: The study outlines the critical elements required to prove economic crimes in construction, including specific methods and criminalistic circumstances. It presents effective strategies for planning investigations, employing tactical methods, and engaging in psychological communication with suspects and accused individuals. Novelty: This article introduces a focused analysis on the economic crimes prevalent in the construction sector, offering new insights into the investigative processes and tactical methods tailored to these types of crimes. Implications: The findings have significant implications for improving investigative practices in economic crimes within the construction industry. The proposed strategies and methods can enhance the effectiveness of investigations, contribute to more accurate crime resolution, and support the development of specialized training for law enforcement and investigative personnel.